y = 20 - 2x

x 0 1 2 3
y  [[20]]   [[18]]   [[16]]   [[14]] 
x 5 6 7  
y  [[10]]   [[8]]   [[6]]   

 

y = 7 - x

x 0 1 2 3
y  [[7]]   [[6]]   [[5]]   [[4]] 
x 5 6 7  
y  [[2]]   [[1]]   [[0]]   

 

y = 2x + 5

x 0 1 2 3
y  [[5]]   [[7]]   [[9]]   [[11]] 
x 4 5 6  
y  [[13]]  [[15]]   [[17]]   

 

y = 2x

x 0 1 2 3
y  [[0]]   [[2]]   [[4]]   [[6]] 
x 6 7 8  
y  [[12]]   [[14]]   [[16]]   

 

y = x + 5

x 0 2 4 5
y  [[5]]   [[7]]   [[9]]   [[10]] 
x 8 9 10  
y  [[13]]   [[14]]   [[15]]   

 

 

y = x + 2

x 0 1 2 5
y  [[2]]   [[3]]   [[4]]   [[7]] 
x 7 9 10  
y  [[9]]   [[11]]   [[12]]